2003
DOI: 10.1001/archsurg.138.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Laparoscopic Colectomy in Older Patients

Abstract: Hypothesis: Few data describe the relative benefits of an expedited recovery program and laparoscopic technique in older vs younger patients undergoing colectomy. We compared short-term outcomes in age-matched cohorts of patients undergoing laparoscopic vs open segmental colectomy managed with the Controlled Rehabilitation With Early Ambulation and Diet program. Design: Four age-matched cohorts of patients were compared: (1) patients 70 years or older undergoing laparoscopic colectomy (group 1), (2) those 70 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 31 publications
10
96
0
3
Order By: Relevance
“…These results are similar to those reported by previous studies, as the operative time of the laparoscopic procedure was reported to be 20-30 min longer compared to laparotomy (9)(10)(11)(12). Only in the study by Senagore et al was the operative time reported to be shorter with LC (14), but no further discussion was offered regarding this finding. Despite the longer operative time, less blood loss and lower transfusion rate demonstrated that LC is safe for elderly patients.…”
Section: Discussionsupporting
confidence: 89%
“…These results are similar to those reported by previous studies, as the operative time of the laparoscopic procedure was reported to be 20-30 min longer compared to laparotomy (9)(10)(11)(12). Only in the study by Senagore et al was the operative time reported to be shorter with LC (14), but no further discussion was offered regarding this finding. Despite the longer operative time, less blood loss and lower transfusion rate demonstrated that LC is safe for elderly patients.…”
Section: Discussionsupporting
confidence: 89%
“…This rate is comparable with published data. 24 There were no deaths in the VE group. Although three deaths occurred in the non-VE cohort, there was no statistical difference between the mortality rates.…”
Section: Discussionmentioning
confidence: 86%
“…A similar pattern has been described in the literature. 24 There was, however, no statistical difference in readmission rates between the two cohorts.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, several studies as mentioned earlier have shown a beneficial short-term effect of laparoscopic colorectal cancer surgery in elderly people [1][2][3][4]. A recent paper dealing with redefining contraindications to laparoscopic colorectal resection for high-risk patients has concluded that in experienced hands, laparoscopic colorectal surgery can be performed safely for these patients and argued against using parameters of increased age, morbid obesity, high ASA class, or preoperative radiation alone as contraindications to even complex laparoscopic colorectal procedures [19].…”
Section: Long-term Results After Laparoscopic Resectionmentioning
confidence: 99%
“…The beneficial short-term effect of laparoscopic colorectal cancer surgery in elderly people with regard to reductions in length of hospital stay, morbidity and mortality rates is shown in several studies [1][2][3][4]. A recent Cochrane analysis of long-term results of laparoscopic colorectal cancer resection concluded that laparoscopic surgery for colon cancer is a safe procedure with a survival rate equal to survival after open surgery, but trials that also include elderly patients with co-morbidity are needed [5].…”
Section: Introductionmentioning
confidence: 99%